2022
DOI: 10.1111/jfbc.14499
|View full text |Cite
|
Sign up to set email alerts
|

The ability of yoghurt supplemented with dietary fibers or brans extracted from wheat or rice to reduce serum lipids and enhance liver function in male hypercholesterolemic rats

Abstract: This study was undertaken to evaluate the effect of yoghurt supplementation with rice and wheat brans or dietary fibers on serum lipid profile, liver, and heart functionalities, and hepatopathological aspects of the liver of hypercholesterolemic rats. 48 male rats were divided into 8 groups. Group 1 was kept as negative control and fed with a standard diet, and groups 2 to 6 were fed a hypercholesterolemia‐induced diet supplemented with brans or dietary fibers of both grains. G2 received yoghurt without supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The AI of hyperlipidemic rats of the PC group, H-RBDF group, N-RBDF group and E-RBDF group decreased to different degrees, in addition the AI of rats in the H-RBDF and E-RBDF groups was significantly lower than that in the MC group (p < 0.05), and the effect of E-RBDF intervention treatment was the best. Similarly, Dabour et al [53] found that yogurt supplemented with wheat bran or dietary fiber significantly (p < 0.05) reduced AI in hypercholesterolemic rats.…”
Section: Effect Of Dietary Fiber On Blood Lipid Level Of Ratsmentioning
confidence: 84%
“…The AI of hyperlipidemic rats of the PC group, H-RBDF group, N-RBDF group and E-RBDF group decreased to different degrees, in addition the AI of rats in the H-RBDF and E-RBDF groups was significantly lower than that in the MC group (p < 0.05), and the effect of E-RBDF intervention treatment was the best. Similarly, Dabour et al [53] found that yogurt supplemented with wheat bran or dietary fiber significantly (p < 0.05) reduced AI in hypercholesterolemic rats.…”
Section: Effect Of Dietary Fiber On Blood Lipid Level Of Ratsmentioning
confidence: 84%
“…In addition, the AI of rats in the H-RBDF and E-RBDF groups was significantly smaller than that in the MC group (p < 0.05), and the effect of E-RBDF intervention treatment was the best. Similarly, Dabour et al [54] found that yogurt supplemented with wheat bran or dietary fiber significantly (p < 0.05) reduced AI in hypercholesterolemic rats. hydraulic-pressed rice bran meal dietary fiber, n-hexane-leached rice bran meal dietary fiber, enzyme-method rice bran meal dietary fiber, respectively.…”
Section: Effect Of Dietary Fiber On Blood Lipid Levels Of Ratsmentioning
confidence: 84%
“…Dabour et al. ( 2022 ) also probed the effects of barley bran and oat bran dietary fibers on liver cholesterol range. This diet (including dietary cholesterol) decreased serum LDL, liver cholesterol, and liver lipid and raised HDL and HDL/LDL cholesterol ratios (Noreen, Tufail, Badar Ul Ain, et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Merali et al found that hydrothermal pretreatment opens wheat bran cell walls, breaks down, solubilizes, and hydrolyzes hemicellulosic arabinoxylans and glucose, and reduces crosslinking phenolic acids (Merali et al, 2015;Tufail et al, 2018;. Dabour et al (2022) also probed the effects of barley bran and oat bran dietary fibers on liver cholesterol range. This diet (including dietary cholesterol) decreased serum LDL, liver cholesterol, and liver lipid and raised HDL and HDL/ LDL cholesterol ratios .…”
mentioning
confidence: 99%